Outcomes of Osteosarcoma in Children Without High-Dose Methotrexate: Could It Be Less Toxic Without Effecting Survival Rates? - TOKUÇ, AYŞE GÜLNUR; EROL, BÜLENT; EKER, NURŞAH; BUĞDAYCI, ONUR (MARY ANN LIEBERT, INC, 2022)
Background: Osteosarcoma (OS) is the most common primary bone sarcoma in childhood. High-dose methotrexate, doxorubicine, cisplatin, and/or ifosfamide combinations are used as standard treatment in chemotherapy and could cause serious toxicity. Another alternative chemotherapy protocol is consisting of epirubicin, ifosfamide, and cisplatin (ECI), which we use in our center. The aim of this study was to evaluate the patients with OS who were treated with ECI protocol, retrospectively. Methods: Forty-three patients with OS diagnosed at our center between December 1995 and September 2017 were evaluated retrospectively. Results: The mean follow-up period was 31 months (5-145 months). Recurrence was detected in 15 of 43 patients. When the factors affecting relapse are examined, recurrence was higher in patients who were older than 10 years at the time of diagnosis, upper extremity involvement, osteoblastic, and chondroblastic subgroups, but there was no statistically significant difference. Five-year and 10-year overall survival rates were 67.4% and 58.9%, and event-free survival rates were 54% and 47.3%, respectively. While 5-year overall survival rate was 86.7% in nonrecurrent cases, this rate was 40.9% in recurrent cases and this difference was statistically significant (p = 0.023). Just two patients died because of the toxicity. Conclusion: The prognosis of OS is still poor in relapse cases, so the choice of chemotherapy for neoadjuvant and adjuvant therapy is vital. When the risk of toxicity is also considered, the first step of ECI protocol is seen as a preferable treatment option because the survival rates are similar to the literature.
Keywords: osteosarcoma; children; chemotherapy; METASTATIC OSTEOSARCOMA; NEOADJUVANT CHEMOTHERAPY; IFOSFAMIDE; TRIAL; CISPLATIN; DOXORUBICIN; RADIOTHERAPY; EURAMOS-1; PROGNOSIS; EXTREMITY